A MODEL FOR ASSESSING THE RISK OF A DELAYED WOUND HEALING IN OBESE PATIENTS - E.P. SUKHOPAROVA; I.E. KHRUSTALYOVA; E.V. ZINOVIEV; E.S. KNYAZEVA (Avicenna Tajik State Medical University, 2023)
Objective: Develop a model for predicting the risk of a delayed and complicated course of wound healing in obese patients Methods: The study included 49 patients above 30 years of age (mean age 46.98±7.10 years) with a body mass index (BMI) above 25 kg/m2 (mean value 31.64±5.04 kg/m2 ), who underwent augmentation mammaplasty and aesthetic anterior abdominal wall reconstruction in the period from 2016 to 2018. In the postoperative period, the patients were divided into three groups depending on the wound healing pattern: Group I - complicated wound healing (n=21; 42.86%); Group II - delayed wound healing (n=16; 32.65%); Group III - standard wound healing (n=12; 24.49%). The assessment of the prognostic risk of developing a delayed and complicated wound healing was carried out using a new mathematical model, taking into account the insulin level (mIU/l) and spontaneous secretion of interleukin-1β (pg/ml). Logistic regression analysis was used to determine the significance of prognostic factors. The decision tree model was used to stratify risk groups. A receiver operating characteristic (ROC) analysis was used to assess the quality of the constructed model. Results: Using the decision tree, three risk classes of delayed and complicated wound healing were identified. The highest risk of developing postoperative wound complications (risk=95.0%, n=20) was observed in patients with insulin levels ≥14.0 mIU/l. The average level of risk was determined at the value of insulin <14.0 mIU/l and spontaneous production of interleukin-1β ≥51.0 pg/ml (risk=50.0%, n=2). The lowest risk level of complications (risk=3.7%, n=27) was found with a combination of factors: insulin <14.0 mIU/l and interleukin-1β spontaneous production <51.0 pg/ml. The predictive quality of the constructed model is high (the area under the ROC curve is 0.98). Conclusion: The proposed prognostic model will allow the identification of patients with a high risk of delayed or complicated wound healing in the preoperative period and timely adjust the treatment tactics.